Improving instructional effectiveness with computer-mediated communication - Som Naidu; John Barrett; Peter Olseb (Association for Learning Technology, 1995)
A critical question that often faces educational technologists is how to deliver excellence in teaching and subject-matter content to learners. A corollary to this question is how and what instructional technologies can be brought to address this search for particular contexts? While there is a wide range of instructional delivery technologies we can choose from, our choice must be carefully considered. The number of factors to be considered are too many to list here, but must include a cognizance of the nature of the content or skill that comprises the subject matter of instruction, the learners, the time and their place of study, and the costs of the delivery mode, both for the learners and the institution. This paper reports our experience of the first phase of a three-phased integration of Computer- Mediated Communication (CMC) aimed at improving instructional effectiveness.